Implementation of Inquiry Method in Improving Students' Critical Thinking Skills in Islamic Religious Education Learning at SDN Cipanas 3 - Rahman Alfiansyah; Euis Latipah; Farhan Sofiandi; Fahir Ali (Classroom: Journal of Islamic Education, 2025)
This study aims to describe the implementation of the inquiry method in improving students' critical thinking skills in Islamic Religious Education (PAI) learning at SDN Cipanas 3. This study is motivated by the importance of developing critical thinking skills as part of the 21st century competencies that support students' intellectual abilities and character. The research method used is a descriptive qualitative approach, with data collection techniques in the form of observation, documentation, and reflection on the learning activities of grade V students. This study shows that the application of the inquiry method is able to create an active, participatory, and reflective learning atmosphere. Students who are involved in various stages of inquiry such as asking questions, collecting information, analyzing data, and drawing conclusions in this method encourage students to think logically, analytically, and are able to express opinions argumentatively. In this case, the teacher acts as a facilitator who also supports the dialogic and meaningful learning process. This study confirms that the inquiry method is effectively used in PAI learning to foster critical thinking skills as well as appreciation of Islamic values.